(untitled) (World Science, 2020)
The high professionalism of the teacher invariably remains the decisive criterion for the fulfillment of his social functions. Teacher didactic training is a basic professional quality. The question of the effectiveness of the organization of the process of vocational guidance in the light of the problems under consideration can be successfully resolved on the basis of determining the basic pedagogical abilities and skills that graduates must be formed to successfully overcome the difficulties encountered in the educational process. Before describing the basic abilities in the activities of a young teacher, it is necessary to highlight the functions of his activities, which are discussed in the article, which highlights the methodology for studying the level of didactic knowledge, skills of graduates of a pedagogical university.